A new species of Ituglanis Costa & Bockmann, 1993 (Siluriformes: Trichomycteridae) endemic to the Tramandaí–Mampituba ecoregion, southern Brazil - Ferrer, Juliano; Donin, Laura M.; Malabarba, Luiz R. (Zootaxa, 2015)
Ituglanis boitata, new species, is described from the rio Tramandaí system and rio Mampituba and Araranguá basins, southern Brazil. This new species is distinguished from congeners with the exception of I. bambui, I. boticario,                       I. paraguassuensis and I. proops by the supraorbital canal of the cephalic laterosensory system interrupted between nasal and frontal sections and the presence of pore s2 (vs. supraorbital canal uninterrupted and pore s2 absent). Ituglanis boitata     differs from these species in osteological characters, measurements and body coloration. Ituglanis boitata presents a              noticeable endemism in the Tramandaí–Mampituba freshwater ecoregion, a recognized biogeographic unit for freshwater fishes including other 22 endemic species. A discussion about the intraspecific variation in the cephalic laterosensory system within Trichomycterinae is also provided.